2014
DOI: 10.1021/om4010077
|View full text |Cite
|
Sign up to set email alerts
|

Triazaphospholes versus Triazoles: An Investigation of the Differences between “Click”-Derived Chelating Phosphorus- and Nitrogen-Containing Heterocycles

Abstract: A new class of pyridyl-functionalized triazaphospholes bearing either t Bu or SiMe 3 substituents at the 5-position of the N 3 PC heterocycle have been prepared via the "click" reaction starting from 2-(azidomethyl)pyridine and the corresponding phosphaalkynes. In order to investigate the electronic structure and donor−acceptor properties of such novel chelating and low-coordinate phosphorus heterocycles, calculations at the DFT level have been carried out. Moreover, cyclic voltammetry measurements were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 39 publications
3
34
0
3
Order By: Relevance
“…Interestingly, the reaction of trimethylsilylphosphaethyne with 2-(azidomethyl)pyridine also proceeded straightforwardly, leading for the first time to a TMS-substituted triazaphosphole derivative via this synthetic pathway. 52 As the phosphinine-based P,N ligand 5 undergoes a facile reaction with [Re(CO) 5 Br] under formation of the complex 20, the coordination chemistry of 37 and 38 toward Re(I) was investigated accordingly, and complex [Re(CO) 3 Br(37)] (39) could be characterized crystallographically. The molecular structure of 39 in the crystal is shown in Figure 28, revealing that the chelating ligand 37 coordinates to the Re(I) center via the nitrogen atom N(2) of the triazaphosphole moiety, rather than via the phosphorus atom.…”
Section: Pyridyl-functionalized 3h-1234-triazaphospholesmentioning
confidence: 99%
“…Interestingly, the reaction of trimethylsilylphosphaethyne with 2-(azidomethyl)pyridine also proceeded straightforwardly, leading for the first time to a TMS-substituted triazaphosphole derivative via this synthetic pathway. 52 As the phosphinine-based P,N ligand 5 undergoes a facile reaction with [Re(CO) 5 Br] under formation of the complex 20, the coordination chemistry of 37 and 38 toward Re(I) was investigated accordingly, and complex [Re(CO) 3 Br(37)] (39) could be characterized crystallographically. The molecular structure of 39 in the crystal is shown in Figure 28, revealing that the chelating ligand 37 coordinates to the Re(I) center via the nitrogen atom N(2) of the triazaphosphole moiety, rather than via the phosphorus atom.…”
Section: Pyridyl-functionalized 3h-1234-triazaphospholesmentioning
confidence: 99%
“…We recently demonstrated that methylene-bridged triazaphospholes of type B (Figure 1) and the corresponding phosphorus-lacking triazoles underwent af acile reaction with Re(CO) 5 Br to form complexes[ (N^N)Re(CO) 3 Br]. [5] We therefore also decided to explore the coordination chemistry of 1a and 6a towards Re I because those bidentate ligands were expected to coordinate in ac helating manner to at ransition-metal centre, in contrastt oc ompounds 2-4.A tthe same time, the [Re(CO) 3 Br] metal fragment offers the possibility of investigating the electronic properties of the ligands by meanso fI R spectroscopy of the resulting coordination compounds.…”
Section: Coordination Chemistrymentioning
confidence: 99%
“…[5] We therefore also decided to explore the coordination chemistry of 1a and 6a towards Re I because those bidentate ligands were expected to coordinate in ac helating manner to at ransition-metal centre, in contrastt oc ompounds 2-4.A tthe same time, the [Re(CO) 3 Br] metal fragment offers the possibility of investigating the electronic properties of the ligands by meanso fI R spectroscopy of the resulting coordination compounds. We first paid attention to the coordination chemistry of the triazaphosphole, which could coordinate in either aPN (J)o ra n N^N (K)f ashion ( Figure 10).…”
Section: Coordination Chemistrymentioning
confidence: 99%
See 2 more Smart Citations